2020
DOI: 10.3390/ijerph17238914
|View full text |Cite
|
Sign up to set email alerts
|

Moral Sensitivity, Empathy and Prosocial Behavior: Implications for Humanization of Nursing Care

Abstract: Humanization of nursing is related to certain social and moral variables. Moral sensitivity, empathy, and prosocial behavior help understand a situation and make decisions that benefit the patient. The objective of this study is to find out how these variables are related, and define the differences in moral sensitivity, empathy, and prosocial behavior in humanization of nursing. We also analyzed the mediating role of empathy in the relationship between moral sensitivity and prosocial behavior. The sample was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 41 publications
4
25
0
1
Order By: Relevance
“…In this study, increased empathy was associated with greater levels of nursing competency, interpersonal relationship ability, and moral sensitivity, which is consistent with the findings of previous research [ 29 , 64 , 65 , 66 ]. Empathy is a vital component of inter-personal relationships and care processes [ 67 , 68 ] and can be facilitated through training interventions [ 69 , 70 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, increased empathy was associated with greater levels of nursing competency, interpersonal relationship ability, and moral sensitivity, which is consistent with the findings of previous research [ 29 , 64 , 65 , 66 ]. Empathy is a vital component of inter-personal relationships and care processes [ 67 , 68 ] and can be facilitated through training interventions [ 69 , 70 ].…”
Section: Discussionsupporting
confidence: 92%
“…Considering the role and importance of moral behavior of nurses in organizational effectiveness, patients' satisfaction with the hospital and their success and job performance, this study was conducted to determine the role of emotional and cognitive empathy, moral metacognition and quality of life in predicting moral behavior of nurses. Findings showed that emotional and cognitive empathy had a positive and significant relationship with moral behavior of nurses, which was consistent with the results of previous studies (6,(9)(10)(11). In explaining these results, it can be said that empathy plays a motivating role in moral behaviors in interpersonal situations.…”
Section: Discussionsupporting
confidence: 92%
“…The four factors influencing ethical behaviors include moral sensitivity (interpreting situations and being aware of ethical challenges), moral judgment (ability to recognize and find different solutions to ethical challenges), moral motivation (having a willingness and commitment to ethical behaviors), and moral personality (insistence on doing moral behaviors) (5). One of the factors related to moral behavior is emotional and cognitive empathy, which is an important concept in the context of social interactions (6). Empathy as a complex and multidimensional concept means the ability to understand others and experience their feelings and cognitions and provide appropriate responses to them, which plays an important role in performing social and moral behaviors (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of ethical decision‐making in clinical education improves the quality of nursing care based on best practice and scientific learning (Amiri et al, 2019 ). Thus, nurses and prospective nurses must be equipped with high moral sensitivity (Liaschenko & Peter, 2004 ; Suazo et al, 2020 ), along with the competence to advocate for patients' rights and dignity.…”
Section: Introductionmentioning
confidence: 99%